The ripple effect: impacts of climate change on menstrual health and paths to resilience - Muralidharan, Arundati; Broekhuijsen, Marije; Lisondra, Lady; Guru, Aeka; Haver, Jacquelyn; Irfan, Sidra (Frontiers in Global Women's Health, 2025)
Girls and women face greater threats and severe ramifications from climate change, with studies consistently finding that women experience more health risks from climate change than men do. Climate change endangers girls and women's sexual and reproductive health and rights, including their menstrual health and hygiene practices. However, menstrual health and hygiene is rarely discussed in the context of climate change. We scoped the existing evidence to describe the interlinkages between climate change and menstrual health and hygiene, and outline services that anticipate, respond to, cope with, recover from, adapt to or transform in response to climate related events, trends and disturbances. Specifically, we describe how climate change disrupts access to essential menstrual health and hygiene information, products and services, impacts menstrual disorders and the menstrual cycle, and intensifies existing inequalities. Recommendations for improvement include climate resilient menstrual health and hygiene services encompassing access to menstrual products and materials, impartment of knowledge and skills, access to climate resilient facilities and services, social support, and policy actions.